Effects of damping and stiffness of AFM cantilever on the imaging of fine surfaces. Issue 10 (3rd August 2016) - Sadeghzadeh, Sadegh; Korayem, M.H.
Abstract: In this paper, by applying the differential quadrature (DQ) method, a semi analytical model has been developed for atomic force microscope cantilever, and then by using the interfacial forces between the cantilever tip and imaged surfaces, a 2D model has been extracted for imaging nano‐sized fine samples. By employing the present model, several simple and standard samples have been imaged, and finally the effects of the microcantilever's structural damping and its stiffness on the imaging results have been investigated. It has been observed that, through the control of damping, the quality of the acquired images is considerably improved. It has also been shown that the self‐softening and self‐hardening properties of cantilever have serious effects on the obtained images. The present model can be used to study the effects of different parameters on the process of imaging small‐scale samples. Also, as one of its most important applications, this model can be used in common multiscale models for simulating and predicting the effects of large and small fields on each other.